Valor intrínseco terapéutico de medicamentos dispensados en una Corporación farmacéutica de la ciudad de Trujillo, abril 2016 – marzo 2017 - De la Cruz Quiroz, Carlos Samuel (2019)
The objective of the report is to determine the intrinsic therapeutic value (VIT) of 100 medicines of more dispensing in a pharmaceutical corporation of the city of Trujillo, La Libertad Region, between April 2016-March 2017, in order to contribute to the rational and efficient use of medicines. The database obtained from the system of a pharmaceutical corporation, it served to determine the VIT of the 100 medicines dispensed between April 2016 – March 2017, according to the classification of Laporte that considers the efficacy and safety of medicines. The results indicate that 8%, 19% and 73% of the drugs analyzed in the Pharmaceutical Corporation represent dubious, relative and high values respectively. The monofármacos represent 67% and combinations represent 33%. Multisource represents 60% and 40% represent reference. According to the classification by major groups Anatomical Therapeutic Chemical (ATC) the group J (Anti-infective drugs in general for systemic use) represents the 30%, and G (the genitourinary system and sex hormones) represents the 13%.